Adaptation of the British Sign Language Receptive Skills Test into Polish Sign Language. (January 2021) - Kotowicz, Justyna; Woll, Bencie; Herman, Rosalind
The evaluation of sign language proficiency needs to be based on measures with well-established psychometric proprieties. To date, no valid and reliable test is available to assess Polish Sign Language ( Polski Język Migowy, PJM) skills in deaf children. Hence, our aim with this study was to adapt the British Sign Language Receptive Skills Test (the first standardized test to determine sign language proficiency in children) into PJM, a less researched sign language. In this paper, we present the first steps in the adaptation process and highlight linguistic and cultural similarities and differences between the British Sign Language Receptive Skills Test and the PJM adaptation. We collected data from 20 deaf children who were native signers (age range: 6 to 12) and 30 deaf children who were late learners of PJM (age range: 6 to 13). Preliminary analyses showed that the PJM Receptive Skills Test has acceptable psychometric characteristics (item analysis, validity, reliability, and sensitivity to age). Our long-term goal with this work was to include younger children (age range: 3 to 6) and to standardize the PJM Receptive Skills Tests, so that it can be used in educational settings and in scientific research.